“Molecular pigeon” network of lncRNA and miRNA: decoding metabolic reprogramming in patients with lung cancer - Li, Mingxiao; Dai, Ling; Chen, Simin; Deng, Minjie; Wang, Lihuai; Sun, Yinhui (Frontiers in Oncology, 2025)
In recent years, with the advancement of RNA analysis techniques, such as single-cell RNA sequencing, noncoding RNAs have demonstrated substantial potential in regulating gene expression, encoding peptides and proteins, constructing the cellular microenvironment, and modulating cell function. They can serve as potential therapeutic targets and diagnostic markers for various diseases, offering novel avenues for diagnosis and treatment. Among them, long noncoding RNAs (lncRNAs) represent a principal component. Through the competing endogenous RNA mechanism, lncRNAs sequester microRNAs (miRNAs), interact with metabolic enzymes or transcription factors, regulate gene expression, and participate in the metabolic communication network within the tumor microenvironment. This process significantly promotes the growth, proliferation, and metastasis of lung cancer cells by reprogramming core metabolic pathways—including glucose utilization, lipid homeostasis, and amino acid flux. This article reviews the key roles of lncRNAs and miRNAs in the metabolic reprogramming of patients with lung cancer, elucidates the complex lncRNA–miRNA network involved, and provides mechanistic insights into metabolic vulnerabilities and translational opportunities for targeted interventions in the diagnosis and treatment of lung cancer.